2014
DOI: 10.1007/978-3-662-43619-6_4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Manipulations for Enhancing Luminescent Bioreporters Performance in the Detection of Toxic Chemicals

Abstract: Microbial whole-cell bioreporters are genetically modified microorganisms that produce a quantifiable output in response to the presence of toxic chemicals or other stress factors. These bioreporters harbor a genetic fusion between a sensing element (usually a gene regulatory element responsive to the target) and a reporter element, the product of which may be quantitatively monitored either by its presence or by its activity. In this chapter we review genetic manipulations undertaken in order to improve biolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Express methods based on microbial wholecell bioreporters are the most promising among them for use in drug toxicology. Microbial whole-cell bioreporters are genetically modified micro-organisms that produce a quantifiable output in response to the presence of toxic chemicals or other stress factors (14).…”
mentioning
confidence: 99%
“…Express methods based on microbial wholecell bioreporters are the most promising among them for use in drug toxicology. Microbial whole-cell bioreporters are genetically modified micro-organisms that produce a quantifiable output in response to the presence of toxic chemicals or other stress factors (14).…”
mentioning
confidence: 99%
“…The genotype of chassis strains can profoundly affect the performance of the sensing pathways carried (Yagur-Kroll and Belkin, 2014). For example, Julien et al observed a 10-fold increase in sensitivity of nickel-iron WCB when E. coli TD2158 was used as a chassis instead of E. coli K12 (Cayron et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, based on the traditional luminescent bacteria bioassay, two new detection methods are proposed. One involves using genetic engineering to transfer the structural genes responsible for luminescence to other bacteria and assemble them into recombinant luminescent bacteria, which can realize the detection of specific pollutants [27,28]. The other is to use magnetic nanomaterials and luminescent bacteria to assemble magnetic nanoparticles (MNPs)-based biosensors, which can be separated from the soil solution and tested under an external magnetic field, without centrifugation and other operations, to realize the detection of undisturbed soil [29].…”
Section: Introductionmentioning
confidence: 99%